Distribution system loss minimization through optimization of substation primary feeder routing using genetic algorithm - De Claro, Mark Wayne C. (2004)
This research aims to minimize the annual loss of a given distribution system considering the feeder cost through an optimization method using Genetic Algorithm (GA). Genetic Algorithm is based on the mechanics of natural selection and natural genetics. This method is more efficient than conventional optimization methods due to elimination of several assumptions used by the later. The optimization of the feeder route as well as its subsequent loadflow analysis was implemented in C++ and was performed on the modified versions of the IEEE 37 and 123-node buses. The algorithm used three basic GA operators: selection, crossover, and mutation which provided a search capability that resulted in an improved quality of solution and enhanced rate of convergence. The project was able to obtain optimal results for the IEEE 36-node test system as well as for the 122-node test system as compared to the original configuration.